Germany In An Interconnected World Economy - Mody, Ashoka (International Monetary Fund, 2013)
Germany has been a central player in discussions on the future architecture of Europe, and has been called on to play a larger role in supporting global and, especially, European recovery from the financial crisis that triggered the Great Recession. This book focuses on the possible economic role of Germany and shows that the quantitative effects of a German fiscal stimulus would be small on the heavily indebted euro area periphery countries that most need the boost. The book finds that Germany itself faces a growth challenge and that efforts to raise its own growth potential are important for Germany, and that more rapid growth of domestic demand will more powerfully stimulate European economic growth through its expanded demand for imports.